The Influence of Halal Labels, Product Quality, and Social Media Marketing on Consumer Interest in Buying Halal Products - Nurhayani Nurhayani (Universitas Serang Raya, 2026)
This study aims to examine the influence of Halal Labeling, Produk Quality, and Social Media Marketing on the Puechase Imntention Of Cosmetics Among Generation Z. The study employs a quantitative research method using a survey approach through the distribution of questionnnaires to respondents. A total of 100 respondents participated in this research. The sampling technique used was purposive sampling. Data were analyzed using SPSS. Statistical Analyses included validity testing, reliability testing, multiple linear regression analysis, t-tests (partial tests), F-test (simultaneous tests), and the coefficient of determination. The results of the study reveal that the variables of Halal Labeling, Product Quality, and Social Media Marketing each have a positive and significant effect on Purchase Intention of Cosmetics Among Generation Z.